Pengembangan Sumber Daya Manusia Berbasis Kewirausahaan Sosial di Yayasan Tajaul Karomah Desa Situ Gadung Tangerang - Dira Karlina; Widowati Widowati; Windy Gustia Wardani (Jurnal PKM Manajemen Bisnis, 2026)
Human resource development is essential for empowering communities and fostering sustainable social entrepreneurship, particularly in rural areas where access to knowledge and practical skills remains limited. Yayasan Tajaul Karomah in Desa Situ Gadung, Tangerang, faces challenges in optimizing the capabilities of its teachers and students to initiate socially beneficial entrepreneurial activities. This community service activity aimed to enhance human resource competencies based on social entrepreneurship by providing knowledge, practical skills, and motivation to teachers and students to engage in socially-oriented business initiatives. The program was implemented at Yayasan Tajaul Karomah on October 4–5, 2025, by a team of nine lecturers from Universitas Pamulang and involved 32 participants, including teachers and students. The methodology combined lectures, hands-on practice, interactive discussions, and question-and-answer sessions, ensuring participants could understand theoretical concepts and directly apply them in practical scenarios. As a result, participants demonstrated significant improvement in understanding social entrepreneurship principles, business planning, problem-solving, and community engagement. They also expressed increased motivation to develop sustainable entrepreneurial projects that generate social impact, while discussions facilitated the exchange of creative ideas and strategies tailored to the local context. The activity successfully contributed to strengthening human resources, promoting social entrepreneurship awareness, and laying the foundation for ongoing community empowerment initiatives at the foundation and surrounding areas.